(untitled) (Research, Society and Development, 2023)
The study aimed to investigate the availability for interprofessional learning and the development of collaborative competencies for teamwork in the Bridges Project in the context of COVID-19. This is a descriptive, exploratory, and cross-sectional study with a mixed qualitative and quantitative approach, developed through the application of the Readiness for Interprofessional Learning Scale (RIPLS) with questions to characterize the profile and semi-structured online interviews with undergraduate and graduate students from different health areas who participated in the management of the Pontes Project between 2020 and 2021. The interviews were recorded, transcribed and analyzed using the thematic content analysis technique. The study included 11 undergraduate students (2 from Dentistry and 9 from Medicine) and 2 postgraduate students from Occupational Therapy, most of whom were women aged 23 years on average. It was observed that students are in a comfort zone with availability for interprofessional learning, that the factors "Teamwork" and "Health Care" are directly proportional and that there was no statistical significance when comparing the responses of the medical course and the other areas. The qualitative data were organized into the following themes: learning from the other, dialogicity, educational possibilities, and commitments and learning from user-centered care. The context of interprofessional learning with user-centered care contributed to the development of collaborative competencies and favored the strengthening of inclusive public policies that proved to be even more necessary within the context of COVID-19.